Brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine in patients with advanced-stage, classical Hodgkin lymphoma: A prespecified subgroup analysis of high-risk patients from the ECHELON-1 study - Hutchings, Martin; Radford, John; Ansell, Stephen M; Illés, Árpád; Sureda, Anna; Connors, Joseph M; Sýkorová, Alice; Shibayama, Hirohiko; Abramson, Jeremy S; Chua, Neil S; Friedberg, Jonathan W; Kořen, Jan; et al. (Hematological oncology, 2021)
Approximately one-third of patients diagnosed with Hodgkin lymphoma presenting with Stage IV disease do not survive past 5 years. We present updated efficacy and safety analyses in high-risk patient subgroups, defined by Stage IV disease or International Prognostic Score (IPS) of 4-7, enrolled in the ECHELON-1 study that compared brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine (A + AVD) versus doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) as first-line therapy after a median follow-up of 37.1 months. Among patients treated with A + AVD (n = 664) or ABVD (n = 670), 64% had Stage IV disease and 26% had an IPS of 4-7. Patients with Stage IV disease treated with A + AVD showed consistent improvements in PFS at 3 years as assessed by investigator (hazard ratio [HR], 0.723; 95% confidence interval [CI], 0.537-0.973; p = 0.032). Similar improvements were seen in the subgroup of patients with IPS of 4-7 (HR, 0.588; 95% CI, 0.386-0.894; p = 0.012). The most common adverse events (AEs) in A + AVD-treated versus ABVD-treated patients with Stage IV disease were peripheral neuropathy (67% vs. 40%) and neutropenia (71% vs. 55%); in patients with IPS of 4-7, the most common AEs were peripheral neuropathy (69% vs. 45%), neutropenia (66% vs. 55%), and febrile neutropenia (23% vs. 9%), respectively. Patients in high-risk subgroups did not experience greater AE incidence or severity than patients in the total population. This updated analysis of ECHELON-1 shows a favorable benefit-risk balance in high-risk patients.
Keywords: vinblastin; doxorubicin; Male; Brentuximab Vedotin; brentuximab vedotin; Risk Factors; Antineoplastic Combined Chemotherapy Protocols; high risk Hodgkin lymphoma; Neoplasm Staging; Adult; dospělí; mužské pohlaví; Vinblastine; Hodgkin Disease; ECHELON-1; Dacarbazine; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; dakarbazin; rizikové faktory; Hodgkinova nemoc; Female; lidé středního věku; staging nádorů; Doxorubicin; Middle Aged